Innovation in the management of social investment projects (Revista de Investigaciones Universidad del Quindío, 2023)
This article makes a systematic review in multiple databases about bibliography in professional journals on innovation in social investment projects; 60 articles were selected and after sorting them out (applying exclusion criteria) there were selected 20 (12 of international scope and 8 Colombian).It is proposed a qualitative descriptive analysis of the main characteristics of the innovation projects and it's social investment nature, applying said analysis of innovative work beginning from international data and containing social investment components and thereby reaching Colombian current narrative and it's impact both in private as in public spaces.Results of this review show that in an international scenario, developed countries' governments are increasingly making investments in innovative projects on a variety of topics that establishments such as universities are leading, therefore recruiting more human resources that multiply this tendency and creating institutions that verify and keep track of those projects. Meanwhile, in Colombia, a developing country is yet in the "waiting list" for investment in innovation, moreover, before the COVID-19 pandemic in 2020 there were plenty of projects being carried out in tech sciences and consequently slowed down. As far as this date, those projects are starting to break through again.
Keywords: innovation; project management; social investment; technology; investment